Conflictual and consensual class relations in collective governance: Comparing the expansion of short apprenticeships in Germany and Switzerland. (15th December 2022) - Graf, Lukas
Abstract: Collective skill formation builds on a long tradition of cooperation between state actors, unions, and employer associations. As such, it can be considered strongly path‐dependent, which also refers to deeply institutionalized arrangements reconciling economic and social objectives across public and private actors. Yet, given structural changes in the economy and crises on the training market, dual apprenticeship training has been increasingly challenged to maintain its balance between economic and social objectives. In this context, I analyse the expansion of short‐track dual apprenticeship training, which represents a lower‐cost, lower‐qualification variant of traditional dual apprenticeships in Germany and Switzerland. In these countries—both of which are core examples of collective skill formation systems—such short‐tracks were expanded starting in the early 2000s. However, German unions have heavily opposed this expansion, while Swiss unions have actively supported it. I carry out a comparative historical‐institutional analysis to address this puzzle and unpack the respective change processes. Focussing on the dominant governance modes, I find that in Switzerland, the expansion of short‐tracks is linked to path reinforcement in terms of a liberal corporatist system characterized by polite employer domination. In contrast, in Germany I observe that the developments around short‐tracks are associated with a path switch from a social to a more liberal collective skill formation arrangement but one that is linked to rather 'hostile' employer domination.